EMPOWERING PERFORMANCE: INVESTIGATING THE EFFECTS OF PSYCHOLOGICAL EMPOWERMENT AND TRANSFORMATIONAL LEADERSHIP ON JOB PERFORMANCE - Sari, Ria Rusdiana; Suwarto, FX (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2025)
This study aims to investigate the effect of psychological empowerment and transformational leadership on job performance, mediated by affective commitment. The study population consisted of employees in the construction industry in Jakarta. The sample in this study was obtained through a purposive sampling method from staff members with permanent employee status and a minimum work tenure of 2 years, resulting in a total of 300 respondents. The data were analyzed using the Structural Equation Modeling (SEM) approach. The findings show that psychological empowerment, transformational leadership, and affective commitment have a direct effect on job performance. Other findings show that psychological empowerment and transformational leadership have an indirect effect on job performance through affective commitment. The managerial implication of this study is to develop and implement psychological empowerment and transformational leadership, thereby increasing employees' affective commitment, which will motivate them and enhance their performance. JEL: M54, O15, L74.